Solve e^(2x) = 5e^(x) - 6, giving your answers in exact form

Solve e2x = 5ex - 6e2x - 5ex + 6 = 0(ex)2 - 5ex + 6 = 0 (Let k = ex)k2 - 5k + 6 = 0(k-3)(k-2) = 0k = 3 k = 2ex = 3 ex = 2x = ln(3) x = ln(3)

Answered by Thomas H. Maths tutor

4233 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

1)Simplify sqrt 98 - sqrt 32, givimg your answer in the form k sqrt 2 where k is an integer.


Solve the equation: 5^(2x+1) = 7, giving your answer correct to four decimal places.


How do you know if a function is odd or even?


Find the value of (cos(x) + sec(x))^2 with respect to x when evauated between pi/4 and 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences